Common pediatric medical procedures. Reduction of simple dislocation - Kelleher, Kelly J.; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2014)
A complete review and demonstration of the procedure for reduction of simple dislocation, including full demonstrations of the procedures for reducing shoulder and patella dislocations.
Presenter: Kelly J. Kelleher.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 16, 2020)
Keywords: Dislocations in children; Children -- Wounds and injuries -- Nursing; Pediatrics; Documentary films; Instructional films; Nonfiction films; Internet videos; Streaming video; Short films